Effects of cooperative–metacognitive instruction on EFL learners' writing and metacognitive awareness. Issue 2 (3rd April 2022) - Teng, Mark Feng
ABSTRACT: This study aims to explore the effects of incorporating metacognitive prompts into cooperative learning on students' academic writing and metacognitive awareness. In total, 150 tertiary-level learners were randomly and equally divided into three groups: a cooperative learning group with metacognitive instruction (EG), a metacognitive instruction group (CG1), and a cooperative learning group (CG2). Participants completed a semester-long intervention. Results revealed that the EG students performed best on academic writing and metacognitive regulation; no significant differences were detected between CG1 and CG2. These findings suggest that significant improvement in metacognitive knowledge was not detected in any group. Relevant implications for teaching writing and understanding EFL learners' metacognitive awareness are discussed.